Atomically dispersed SrOx species on exposed 2 2 2 facets of pyrochlore La2Zr2O7 nanocrystals for boosting low-temperature oxidative coupling of methane. (1st February 2023) - Wu, Tongtong; Wei, Yuechang; Xiong, Jing; Yang, Yitao; Han, Dawei; Zhao, Zhen; Liu, Jian
Graphical abstract: Highlights: Novel catalysts of SrOx supported on 2 2 2 facets of pyrochlore LZO were synthesized. Substitution of La 3+ cations by atomical dispersed SrOx increase surface oxygen vacancies. Surface alkaline sites are beneficial to enhance catalytic performance for OCM reaction. SrOx /LZO-12 catalyst showed excellent catalytic performance for low-temperature OCM. Surface alkaline center promotes critical steps of CH bond breaking and CC bond coupling. Abstract: The efficient catalysts of strontium oxide (SrOx ) supported on exposed 2 2 2 facets of pyrochlore La2 Zr2 O7 nanocrystals (SrOx /LZO-Y) were elaborately synthesized by incipient wetness impregnation method. The introduction of atomically dispersed SrOx species on La2 Zr2 O7 surface can increase the amount of surface oxygen vacancies induced by Sr 2+ substitution of La 3+ cations, and the increasing of moderate surface alkaline sites are beneficial to enhance catalytic performance for oxidative coupling of methane (OCM). The SrOx /LZO-Y catalysts have super catalytic performance during low-temperature OCM reaction. SrOx /LZO-12 catalyst with the highest concentrations of O2 – species exhibits the highest activity and the lowest apparent activation energy (84 kJ mol −1 ) during low-temperature OCM into C2 H4 and C2 H6 ( C 2 ) products, i.e., its CH4 conversion, selectivity and yield of C 2 products at 600 °C are 30.5 %, 47.4 % and 14.5 %, respectively, and its ratio of C2 H4 /C2 H6 products is 0.77. Based on the results of multiple experimental characterizations, the mechanism of SrOx /LZO-Y catalysts for OCM reaction is proposed: the surface alkaline active centers (O2 – ) induced by doping of Sr ions can promote the critical step of CH4 activation significantly during low-temperature OCM reaction. It is a new strategy to develop the low-temperature and high-activity catalysts for OCM in practical application.